-25=5(y-4)

Simple and best practice solution for -25=5(y-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -25=5(y-4) equation:


Simplifying
-25 = 5(y + -4)

Reorder the terms:
-25 = 5(-4 + y)
-25 = (-4 * 5 + y * 5)
-25 = (-20 + 5y)

Solving
-25 = -20 + 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.
-25 + -5y = -20 + 5y + -5y

Combine like terms: 5y + -5y = 0
-25 + -5y = -20 + 0
-25 + -5y = -20

Add '25' to each side of the equation.
-25 + 25 + -5y = -20 + 25

Combine like terms: -25 + 25 = 0
0 + -5y = -20 + 25
-5y = -20 + 25

Combine like terms: -20 + 25 = 5
-5y = 5

Divide each side by '-5'.
y = -1

Simplifying
y = -1

See similar equations:

| 4h-6=10n | | -12m-8=70 | | 0.16666666666(12-6x)=5(x+4) | | 0.33333333333(6y-9)=-2y+13 | | 80=2(n+6) | | -3.3=4.7-4y | | 6/(2a) | | .30=x(.14)+(1-x)(.05) | | 4x-11=15-9x | | -10500x^3+5000=0 | | 6+5z=8+5z | | 102x^2+6y^2+89y-322=0 | | 55x-39x+12=-64 | | -4=-2(5n-2)-8(-7n+1) | | 28-2x=3x+18 | | .03=.14x+.05-05x | | 8+.09m=90 | | G(2)=5-7+2 | | b/0.8=12.6 | | -6m-13=74 | | 6x^2-54x/x-9•7x/6x | | -7.1=2.9-5y | | 10=1.25*p | | g/3.2=4.7 | | g/2=0.5 | | 4r^2=34-10r | | 4(24)=4(20)+4(4) | | (5x+7)+(4x-18)+(3x+2)=x | | 4q+8q+7q-7= | | 9x+x=79 | | 2(6k-7)+6(-3k+1)=22 | | 175+g=118 |

Equations solver categories